Posterior reversible leukoencephalopathy syndrome associated with pazopanib - Förster, Robert; Welzel, Thomas; Debus, Jürgen; Grüllich, Carsten; Jäger, Dirk; Potthoff, Karin (Case reports in oncology, 2013)
A 62-year-old female patient with metastatic renal cell carcinoma under third-line treatment with pazopanib for 8 weeks suddenly developed severe headaches, grand mal seizures and paresis of the left arm in combination with gait instability as well as nausea and vomiting during her vacation abroad. The emergency physician measured systolic blood pressure values over 300 mm Hg and suspected a stroke. The CT imaging without contrast agent in a local hospital did not show any pathologic findings despite bone metastases. The colleagues suspected cerebral metastases or meningeosis carcinomatosa and referred the patient to our department for further diagnostics and treatment planning. An MRI scan ruled out the suspected cerebral metastases or meningeosis carcinomatosa, but showed signs of reversible posterior leukoencephalopathy syndrome (RPLS) in the form of band-like hyperintensities as a sign of cytotoxic edema in the gray and white matter of the left parietal lobe. The patient then reported that similar blood pressure values had been measured shortly after the start of a first-line therapy with sunitinib, so that we discontinued the current treatment with pazopanib. Within 6 days the neurologic symptoms vanished and the patient was discharged. An intermittent hypertension persisted. A follow-up MRI 3 weeks later showed an RPLS-typical cortical infarction in the affected area. RPLS should be considered as the actual reason for neurologic findings in hypertensive patients with known metastatic cancers under tyrosine kinase inhibitor therapy.